B cell repopulation after alemtuzumab induction-transient increase in transitional B cells and long-term dominance of naive B cells. - Heidt, S; Hester, J; Shankar, S; Friend, P; Wood, K (2012)
In organ transplantation, the composition of the B-cell compartment is increasingly identified as an important determinant for graft outcome. Whereas naïve and transitional B cells have been associated with long-term allograft survival and operational tolerance, memory B cells have been linked to decreased allograft survival. Alemtuzumab induction therapy effectively depletes B cells, but is followed by rapid repopulation up to levels exceeding base line. The characteristics of the repopulating B cells are currently unknown. We studied the phenotypic and functional characteristics of B cells longitudinally in 19 kidney transplant recipients, before and at 6, 9 and 12 months after alemtuzumab induction therapy. A transient increase in transitional B cells and cells with phenotypic characteristics of regulatory B cells, as well as a long-term dominance in naïve B cells was found in alemtuzumab-treated kidney transplant recipients, which was not influenced by conversion from tacrolimus to sirolimus. At all time-points after treatment, B cells showed unaltered proliferative and IgM-producing capacity as compared to pretransplant samples, whereas the ability to produce IgG was inhibited long-term. In conclusion, induction therapy with alemtuzumab results in a long-term shift toward naïve B cells with altered phenotypic and functional characteristics.